2012
DOI: 10.1088/0004-637x/754/1/47
|View full text |Cite
|
Sign up to set email alerts
|

HIGH-RESOLUTION VLBA OBSERVATIONS OF THREE 7 mm SiO MASERS TOWARD VX Sgr AT FIVE EPOCHS

Abstract: VX Sgr is a red supergiant at an adopted distance of 1.6 kpc with intense 43 GHz SiO maser emission. In this paper, we present the high-resolution very long baseline interferometry (VLBI) observations of SiO masers toward VX Sgr at five epochs. We used the Very Long Baseline Array to map the J = 1→0 (v = 1, 2) 28 SiO masers and confirmed a ring-like structure. In the first two epochs, the v = 1 masers form a ring, but v = 2 maser spots residing only in the southern and northern regions do not form a complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Here, we find roughly two order of differences in intensity between the two cases. Similarly, the SiO maser emission (v = 1, J = 1-0) of the three well-known nearby RSGs exhibit systematically larger fluxes than RSGs in Wd1: VY CMa, VX Sgr and NML Cyg exhibit the peak intensities of 5.4 Jy, 31.4 Jy and 2.6 Jy (scaled at 3.5 kpc, Boboltz & Claussen 2004;Zhang et al 2012a;Su et al 2012), while W 237 and W 26 exhibit 1.54 Jy and 0.12 Jy, respectively. However, these differences in intensity between nearby RSGs and RSGs associated with Wd1 are partly due to the uncertainty of distances.…”
Section: Results Of the Sio And H 2 O Maser Observationsmentioning
confidence: 91%
“…Here, we find roughly two order of differences in intensity between the two cases. Similarly, the SiO maser emission (v = 1, J = 1-0) of the three well-known nearby RSGs exhibit systematically larger fluxes than RSGs in Wd1: VY CMa, VX Sgr and NML Cyg exhibit the peak intensities of 5.4 Jy, 31.4 Jy and 2.6 Jy (scaled at 3.5 kpc, Boboltz & Claussen 2004;Zhang et al 2012a;Su et al 2012), while W 237 and W 26 exhibit 1.54 Jy and 0.12 Jy, respectively. However, these differences in intensity between nearby RSGs and RSGs associated with Wd1 are partly due to the uncertainty of distances.…”
Section: Results Of the Sio And H 2 O Maser Observationsmentioning
confidence: 91%
“…For example, Richards et al (2012) estimated the radius of the H 2 O maser cloud in VX Sgr to be an order of magnitude larger than those around known AGB stars. Arroyo-Torres et al (2013), based on data from Chiavassa et al (2010) and Su et al (2012), also found that the SiO masers of VX Sgr are located at ~3 stellar radii, while the SiO masers in AGB stars are mostly located at ~2 stellar radii. On the other hand, these results for VX Sgr are consistent with those obtained for other RHGs, for example S Per (Richards et al 2012) andAH Sco (Arroyo-Torres et al 2013).…”
Section: Introductionmentioning
confidence: 93%
“…Similarly, Su et al (2012) found that SiO maser emission forms a ring with a very narrow range of line-of-sight velocities, while Danchi et al (1994) and Monnier et al (2004) used infrared interferometry to infer the presence of a centrosymmetric structure in dust emission with an inner radius of around 60 mas. Schuster et al (2006) found a similar emission region to our data but did not see any significant asymmetry in the optical, attributing a slight deviation from circular symmetry to CCD bleeding.…”
Section: Discussionmentioning
confidence: 98%